Uncloaking cell-impermeant gold nanorods via tumor microenvironmental cathepsin B facilitates cancer cell penetration and potent radiosensitization. (December 2022) - Raghuram, Subhiksha; Mackeyev, Yuri; Symons, Jessica; Zahra, Yasmin; Gonzalez, Valeria; Mahadevan, Krishnan K.; Requejo, Katherinne I.; Liopo, Anton; Derry, Paul; Zubarev, Eugene; Sahin, Onur; Byung-Kyu Kim, Joseph; et al.
Abstract: Major impediments to conveyance of intravenously administered drugs to tumors are biofouling, opsonization, and rapid clearance from the circulation by macrophages and reticuloendothelial phagocytes. Cloaking nanoparticles with stealth epilayers partly overcomes these hurdles but it also foils interactions with tumor cells. Here, we describe the synthesis, characterization, and validation of smart gold nanorods (GNRs) that spontaneously transform from inert passengers in the blood stream to active cell-penetrating nanoparticles within tumors to potently sensitize tumors to radiation therapy. Intrinsically cationic and cell-penetrating GNRs were shielded from phagocytosis with a cloaking polyethylene glycol epilayer containing an intervening cleavable peptide. In the absence of an external trigger, this epilayer is clipped off by the tumor microenvironmental protease, cathepsin B, in colorectal cancers to uncloak and expose the free-circulating native unPEGylated GNR that is readily internalized by cancer cells and turn into immovable small clusters of GNRs. Selective uncloaking of GNRs in the tumor reduced off-target toxicity confirmed by hematologic, biochemical, and histopathological analysis of blood, serum, and normal organs, respectively. Subsequent irradiation led to significant tumor growth delay and improved survival of mice. By addressing multiple barriers to efficient transport and cellular internalization of nanoparticles, our results demonstrate that clinically meaningful radiosensitization can be achieved with rationally designed GNRs.